2013
DOI: 10.1002/pen.23657
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of two mobile amorphous phases in semicrystalline polylactide observed from calorimetric investigations

Abstract: Amorphous phase dynamics in Poly(lactic acid) (PLA) with different crystallinity degrees have been investigated from the vitreous state to the glass transition by means of two calorimetric methods. Temperature Modulated Differential Scanning Calorimetry was used to characterize the heat capacity signals and the average cooperativity length at the glass transition in non‐aged materials. Standard DSC was used to study the physical aging. It is shown that amorphous and fully crystallized PLA exhibit different rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 57 publications
4
46
0
1
Order By: Relevance
“…According to the literature, this observation can be ascribed to a confinement effect, as reported for other semicrystalline polymers. 32,69,71 Rev-C p curves in Figure 5 also point out that the predictions made on the basis of a simple two-phase model (X MA 2ph = 0.34 for Melt isoT Cryst sample and X MA 2ph = 0.56 for Cold isoT Cryst sample) are unfulfilled in the region of the glass transition and that the RAF must be considered. For example, according to the ΔC p (T g ) values estimated from 75 poly(trimethylene terephthalate) (PTT), 8 and poly(3-hydroxybutyrate) (P3HB).…”
Section: Articlementioning
confidence: 92%
“…According to the literature, this observation can be ascribed to a confinement effect, as reported for other semicrystalline polymers. 32,69,71 Rev-C p curves in Figure 5 also point out that the predictions made on the basis of a simple two-phase model (X MA 2ph = 0.34 for Melt isoT Cryst sample and X MA 2ph = 0.56 for Cold isoT Cryst sample) are unfulfilled in the region of the glass transition and that the RAF must be considered. For example, according to the ΔC p (T g ) values estimated from 75 poly(trimethylene terephthalate) (PTT), 8 and poly(3-hydroxybutyrate) (P3HB).…”
Section: Articlementioning
confidence: 92%
“…PLA can crystallize in a, a 0 , b and c forms [6], and crystal perfection, recrystallization and change of modification may result in multiple peaks during heating and sometimes also during crystallization [6]. Even the amorphous phase of semicrystalline PLA has a complicated structure; it is claimed to contain three types of amorphous molecules: the rigid amorphous fraction, the interspherulitic mobile amorphous phase and the intraspherulitic mobile amorphous phase [31].…”
Section: Introductionmentioning
confidence: 98%
“…For an equivalent path of crystallization, T g was higher when crystallizing at 85 C. The shift of T g towards higher values upon crystallization is characteristic of the constrained amorphous phase between crystalline lamellae, which relaxes only at higher temperatures [19,20]. Among crystallized samples, it has been shown that T g also shifts to higher temperatures when the crystallization conditions did not allow a correct decoupling between the amorphous and the crystalline phase [26].…”
mentioning
confidence: 98%
“…The values of C p glass Ta and C p liquid Ta were obtained by prolonging the glass and liquid lines to dynamic glass transition temperature after normalization to the MAF content [18]. When the crystallization is not performed to its maximum extent, the MAF splits into intra-and inter-spherulitic amorphous regions and calorimetric measurements can show two separate signatures within the glass transition temperature range [20]. To overcome the issues related to such a complex molecular mobility landscape, the investigation of the CRR size was limited to the samples having reached their maximum degree of crystallinity.…”
mentioning
confidence: 99%